Nitrogen and boron nutrition in grafted watermelon II: Impact on nutrient accumulation in fruit rind and flesh. - Kemal Yalçın Gülüt (Public Library of Science (PLoS), 2021)
Turkey ranks second in watermelon (Citrullus lunatus L.) production globally and the highest production is witnessed for Çukurova plains the country. Although watermelon is extensively cultivated in the Çukurova region, studies on optimum nitrogen (N) and boron (B) doses for watermelon cultivation are quite limited. This study, evaluated the impact of increasing N (0, 90, 180 and 270 kg ha-1) and B (0 and 2 kg ha-1 B) doses on nutrient uptake in rind (exocarp) and flesh (endocarp) of watermelon fruit. Grafted watermelon variety 'Starburst', widely cultivated in the region was used as experimental material. The concentrations of different macro and micronutrients were analyzed from fruit rind and flesh. Individual and interactive effect of N and B doses significantly altered macro and micronutrients' uptake in rind and flesh. Higher amounts of macro and micronutrients were accumulated in rind than flesh. Nutrients' uptake was increased with increasing N doses, whereas B had limited impact. The accumulated nutrients were within the safe limits for human consumption. The N concentrations of rind and flesh increased with increasing N dose. Similarly, B concentration in rind and flesh and N concentration in rind significantly increased, while N concentration in flesh decreased with B application. It was concluded that 270 kg ha-1 N and 2 kg ha-1 B are optimum for better nutrient uptake in watermelon fruit. Thus, these doses must be used for watermelon cultivation in Çukurova plains of the country.